Zinc Carbenoid-Promoted Methylene Insertion in Saturated Heterocycles: Mechanistic Insights and Reactivity Profiles - Tsuda, Masato; Nakamura, Hiroyuki (Synthesis, 2024)
The ring expansion of saturated heterocycles through methylene insertion into N–O bonds using a zinc carbenoid is described. This transformation is applied to 1,2-oxazetidines and 1,2-oxazolidines, while N-tosylated 1,2-oxazinane affords a ring-opened product. Density functional theory calculations suggest a stepwise reaction mechanism of the ring expansion and elucidate the origins of the different reactivities observed.
Keywords: saturated heterocycles; ring expansion; zinc carbenoid; insertion; DFT calculations